An allocentric rather than perceptual deficit in patient D.F - Schenk, T. (Nature Neuroscience, 2006)
The perception/action model states that vision for perception and vision for action are processed in separate pathways. This model was inspired by observations in patient D.F. who seemed unable to use vision for perceptual tasks while retaining 'normal' visuomotor capacity. I found that D.F.'s performance is preserved in perceptual and visuomotor tasks when the required spatial information is hand-centered and impaired when the information is object-centered.
EPrint Processing Status: Full text deposited in DRO